COMPARISON OF THREE METHODS FOR THE DETECTION OF ROTAVIRUS ANTIGEN IN THE FAECES OF NEW BORN CALVES - M. Odisho, Shoney; A. Muhamad, Nidhal; S. Al- Bana, Antons (The Iraqi Journal of Veterinary Medicine, 1996)
Immunofluorescence on incoulated cell cultures, latex agglutination test and enzyme-linked immunosorbant assay (ELISA) were compared for the detection of rotavirus antigen in faecal sample from new born calves. Rotavirus were detected in 20 faecal sample by immunfluorescence test, latex agglutination test demonstrated rotavirus in 27 faecal sample, and rotavirus were detected in 29 out of 82 faecal sample by ELISA.